Natural resource use, industrialization and climate change in Africa: Blueprints for sustainable regional development - Forbe Hodu Ngangnchi; Nkwetta Ajong Aquilas; Mukete Emmanuel Mbella (Research in Globalization)
Climate crisis continue to animate environmental policy debate and remains a fundamental global concern. While natural resources use and industrialization are main drivers of climate change especially in developing countries like Africa, previous empirical studies have failed to analyze the simultaneous effect of both on climate change. To close this gap, the current study investigates the relationship between natural resources use, industrialization and climate change in Africa. Specifically, this study analyzes the effect of natural resources rents and value added in manufacturing on carbon dioxide emissions. Addressing these issues is important, as the implications of natural resources extraction and industrial development on environmental sustainability cannot be underestimated. This paper is very relevant because of the limited research on comprehensive frameworks that integrate natural resources use with industrialization policies specific to Africa. Using data from 2005 to 2022 for 45 African countries obtained from the African Infrastructural and World Bank databases, and employing the Cross-Sectional Feasible Generalized Least Squares, Driscoll-Kraay effects, Dynamic Driscoll-Kraay effects and Panel Quantile on Quantile regression techniques, the empirical findings revealed that natural resources rents and industrialization adversely contribute to climate change in Africa. Quantitative results show that a 1% increase in natural resource rents increased carbon dioxide emissions by 0.000103% for both Feasible Generalized Least Squares and Driscoll-Kraay estimates and by 0.00813% for the Dynamic Driscoll-Kraay estimates. Furthermore, a 1% increase in value added in manufacturing led to a 0.377% increase in carbon dioxide emissions for both Feasible Generalized Least Squares and Driscoll-Kraay estimates and a 0.157% increase for Dynamic Driscoll-Kraay estimates. The result also shows that the effect of natural resource extraction and industrialization on climate change become negative at both the 25% quantile and 50% quantile. However, this turning point becomes nullified at the 75% and at 90% quantiles. Africa should adopt a green path to natural resource use and industrialization.